Evaluation of deleting crystalline amino acids from low-CP, amino acid-fortified diets on growth performance of nursery pigs from 15 to 25 lb - J E Nemechek; J Usry; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 294 nursery pigs (PIC TR4 x 1050, initially 15.2 lb, 3 d postweaning) were used in a 28-d trial to evaluate the effects on growth performance of eliminating specific crystalline amino acids from a low-CP, amino acid-fortified diet. On d 3 after weaning, pigs were allotted to 1 of 6 dietary treatments. A 2-phase diet series was used, with treatment diets fed from d 0 to 14 and a common diet fed from d 14 to 28. All diets were in meal form. The formulation was based on data from previous trials in which fish meal was replaced with crystalline amino acids in the diet for 15- to 25-lb pigs. The objective of this trial was to determine which amino acids are required in this low-CP, amino acid-fortified diet. The positive control diet contained L-lysine HCl, DL-methionine, L-threonine, L-isoleucine, L-tryptophan, L-valine, L-glutamine, and L-glycine. The 6 treatments were (1) positive control, (2) positive control with L-isoleucine deleted from the diet, (3) positive control with L-tryptophan deleted, (4) positive control L-valine deleted, (5) positive control with L-glutamine and L-glycine deleted, and (6) positive control with L-isoleucine, L-tryptophan, L-valine, L-glutamine, and L-glycine deleted from diet (negative control). There were 7 pigs per pen and 7 pens per treatment. Pigs and feeders were weighed on d 0, 7, 14, 21, and 28 to calculate ADG, ADFI, and F/G. From d 0 to 14, pigs fed the positive control diet had improved (P<0.03) ADG and ADFI compared with pigs fed the negative control or diets with L-tryptophan or L-valine deleted, with pigs fed the diet without crystalline glutamine and glycine being intermediate. The pigs fed the diet containing no crystalline isoleucine had similar (P>0.40) ADG, ADFI, and F/G to pigs fed the positive control, but had improved (P<0.03) ADG compared to the pigs fed the other 4 diets. For unknown reasons, when the common diet was fed from d 14 to 28, the deletion of crystalline isoleucine in the previous period caused a decrease (P<0.01) in ADG compared to the positive control. Pigs from the other treatment groups had similar (P>0.12) ADG to the positive control. There were no differences (P>0.10) in ADFI from d 14 to 28. Because of the decrease in ADG from d 0 to 14, pigs fed the negative control or diets without L-tryptophan or L-valine had decreased (P<0.04) ADG for the overall trial (d 0 to 28) compared to pigs fed the positive control. ADFI from all treatment diets decreased compared to the positive control, although only the negative control group tested significantly (P<0.04). There was no difference (P>0.24) in F/G for the overall data. In conclusion, L-tryptophan and L-valine were needed in the low-CP, high amino acid-fortified nursery diet to achieve maximum growth performance from 15 to 25 lb. This suggests that the tryptophan:lysine and valine:lysine requirements are greater than 15 and 57% of lysine, respectively. The numerical decrease in performance when L-glutamine and L-glycine were removed from the diet during the first period suggests a need for nonessential nitrogen in the low-CP, amino acid-fortified diet or a benefit to one of these amino acids separate from its role as a nitrogen source.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Amino acid requirement; Glutamine; Glycine; Isoleucine; Tryptophan; Valine